2010
DOI: 10.1371/journal.pone.0008607
|View full text |Cite
|
Sign up to set email alerts
|

Fish as Reservoirs and Vectors of Vibrio cholerae

Abstract: Vibrio cholerae, the etiologic agent of cholera, is autochthonous to various aquatic environments, but despite intensive efforts its ecology remains an enigma. Recently, it was suggested that copepods and chironomids, both considered as natural reservoirs of V. cholerae, are dispersed by migratory waterbirds, thus possibly distributing the bacteria between water bodies within and between continents. Although fish have been implicated in the scientific literature with cholera cases, as far as we know, no study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 32 publications
6
143
0
2
Order By: Relevance
“…The common nase, which was the most severely affected species, is not a typical benthophage, but its pathological relevance is linked to the fact that while scraping algae off hard surfaces it also eats, besides the biofilm, the organisms present in the benthic fauna. This feeding habit is not uncommon in the nase, as observed on many occasions at other sites and the hypothesis is in keeping with the findings of Senderovich et al (2010) and Halpern et al (2008), referred to above. They suggested that fish serve as an intermediate vector of V. cholerae since they create a link in the food chain between chironomids and copepods on the one hand and water birds on the other.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The common nase, which was the most severely affected species, is not a typical benthophage, but its pathological relevance is linked to the fact that while scraping algae off hard surfaces it also eats, besides the biofilm, the organisms present in the benthic fauna. This feeding habit is not uncommon in the nase, as observed on many occasions at other sites and the hypothesis is in keeping with the findings of Senderovich et al (2010) and Halpern et al (2008), referred to above. They suggested that fish serve as an intermediate vector of V. cholerae since they create a link in the food chain between chironomids and copepods on the one hand and water birds on the other.…”
Section: Discussionsupporting
confidence: 91%
“…Du Preez et al (2010) conducted a study to determine whether the estuarine and freshwater environment in Beira, Mozambique, serves as a reservoir of Vibrio cholerae O1 and doi: 10.17221/7921-VETMED O139. Senderovich et al (2010) found that fish of various species and habitats contain V. cholerae non-O1/ non-O139 in their digestive tract. They suggested that fish serve as intermediate vectors of V. cholerae since they create a link in the food chain between chironomidae and copepods on the one hand and waterbirds on the other (Halpern et al 2008).…”
mentioning
confidence: 99%
“…Cholera vibrios are commonly transmitted to humans through ingestion of contaminated food or water, and the disease occurs mainly in developing countries with inadequate sanitation [5][6][7]. Studies have suggested that fish may act as reservoirs and vectors of V. cholerae [8]. While an estuarine environment represents an ideal setting for the survival and persistence of V. cholerae, cholera has also become endemic in arid and inland areas of Africa [9] such as Burkina Faso [10].…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio alginolyticus and Vibrio cholerae are major pathogens in Chinese aquatic products [15]. Senderovich et al [42] isolated Vibrio cholera from Oreochromis aureus; Rehulka et al [43] isolated pathogenic Vibrio cholerae non-O1/non-O139 from moribund freshwater fish, and proved its ability to induce disease condition through experimental infection of common carp, infected carb developed typical signs of Vibriosis. Unidentified pathogenic bacteria represent 3.3% (one out of 30 isolates).…”
Section: Alginolyticusmentioning
confidence: 99%